Taking the "black pill": anomie, perceived social death, and the incel phenomenon online - Puhrmann, Aaron (Deviant behavior, 2024)
Research on incels has largely focused on economic theory, misogyny that incels display in online forums, or their potential threat of violence. This paper proposes to look at the incel phenomenon through the lens of sociological theory, specifically through the lens of social death which the researchers are calling "perceived social death." This research focuses on incels who have adopted a "black pill" identity and express a form of perceived social death in which black-pilled incels believe themselves to be involuntarily disengaged from society to live as socially dead individuals. Black pillers are often described as a more nihilistic incel identity but such a description does not capture the complexity and nuanced differences between different forms of incels. The researchers looked for themes of social death through online postings in known incel forums to gain a better understanding of the social forces that push these individuals to adopt the label of "incel."